Tensiomyography reliability and prediction of changes in muscle force following heavy eccentric strength exercise using muscle mechanical properties - de Paula Simola, R. A.; Harms, N.; Raeder, C.; Kellmann, M.; Meyer, T.; Pfeiffer, M.; Ferrauti, A. (Sports Technology, 2015)
The current study involved the completion of two distinct experiments. Experiment 1 analyzed the inter-day reliability of tensiomyography (TMG) muscle mechanical properties based on the amplitude of the muscle belly radial deformation, the time it takes to occur, and its velocity under maximal and submaximal stimuli, in the muscles rectus femoris, biceps femoris, and gastrocnemius lateralis, from 20 male sport students. Experiment 2 investigated whether changes in maximal voluntary isometric contraction (MVIC) could be predicted based on changes in TMG properties following 24 h after different squat training protocols (MS = multiple sets; DS = drop sets; EO = eccentric overload; FW = flywheel; PL = plyometrics) executed by 14 male strength trained athletes. Maximal electrical stimulation exhibited higher level of reliability. In most of the cases, TMG properties Tc, Td, Dm, V10, and V90 showed ICC scores >.8 and CV <10%. Simple linear regression analysis revealed that changes in Dm, V10, and V90 correlated with changes in MVIC following EO at r = .705, .699, and .695, respectively. TMG is a reliable method to assess muscle mechanical properties particularly within maximal stimuli and can be used for prediction of changes in MVIC following heavy eccentric strength exercises.